2016
DOI: 10.1016/j.ebiom.2016.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Radiogenomics Monitoring in Breast Cancer Identifies Metabolism and Immune Checkpoints as Early Actionable Mechanisms of Resistance to Anti-angiogenic Treatment

Abstract: Anti-VEGF antibody bevacizumab has prolonged progression-free survival in several cancer types, however acquired resistance is common. Adaption has been observed pre-clinically, but no human study has shown timing and genes involved, enabling formulation of new clinical paradigms.In a window-of-opportunity study in 35 ductal breast cancer patients for 2 weeks prior to neoadjuvant chemotherapy, we monitored bevacizumab response by Dynamic Contrast-Enhanced Magnetic Resonance [DCE-MRI], transcriptomic and pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Non-parametric rank product (R package and version) was used to discover the genes with consistent statistically significant fold change (probability of false positive < 0.05) between pre- and post-metformin treatment, among all patients were selected. This approach was preferred with respect to EdgeR ( Anders and Huber, 2010 ) and Deseq ( McCarthy et al., 2012 , Robinson et al., 2010 ) as in datasets with high variability and paired samples (pre and post- treatment) non parametric methods tend to work better in our previous studies ( Mehta et al., 2016 ); however analysis with EdgeR (version 3.16.5) and Deseq (version 1.26.0) was also done and did not change the main conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…Non-parametric rank product (R package and version) was used to discover the genes with consistent statistically significant fold change (probability of false positive < 0.05) between pre- and post-metformin treatment, among all patients were selected. This approach was preferred with respect to EdgeR ( Anders and Huber, 2010 ) and Deseq ( McCarthy et al., 2012 , Robinson et al., 2010 ) as in datasets with high variability and paired samples (pre and post- treatment) non parametric methods tend to work better in our previous studies ( Mehta et al., 2016 ); however analysis with EdgeR (version 3.16.5) and Deseq (version 1.26.0) was also done and did not change the main conclusions.…”
Section: Methodsmentioning
confidence: 99%
“…To increase insight into underlying genomics of MR-perfusion parameters a study associated gene expression profiles with a heterogeneous centripetal perfusion phenotype [ 116 ] and another study associated perfusion parameters with regulatory non-coding transcripts of RNA associated with early metastasis [ 126 ]. Radiogenomics was applied for monitoring of anti-VEGF treatment by measuring pre- and post-treatment perfusion and associated differential gene expression [ 119 ]. Additionally, a qualitative imaging model including tumor heterogeneity and enhancement predicted expression of immune-response genes [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study of DCE-MRI performed before and after a dose of bevacizumab, an antibody that inhibits angiogenesis, showed that the K trans of the tumor on pretreatment MRI was the strongest predictor of response to therapy, and that tumors with good response had downregulation of angiogenesis gene signatures. 128 A study of DCE-MRI in locally advanced breast cancer patients found that the centripetal enhancement pattern is associated with increased expression of PARP6. 129 FIGURE 14: A 52-year-old woman with triple-positive (ER, PR, and HER2-positive) high-grade invasive ductal carcinoma evaluated with breast MRI before and after four cycles neoadjuvant chemotherapy (a: first postcontrast subtraction, b: T 2 -weighted).…”
Section: Future Directionsmentioning
confidence: 99%